(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This study examines the concept of friendship as a culture-bound semantic and cognitive construct in Uzbek and English and explores its implications for comparative translation studies. Building on cognitive linguistics, linguoculturology, and functional approaches to translation, the research argues that apparent lexical equivalence (e.g., do‘st – friend) often conceals conceptual asymmetry rooted in divergent value systems and communicative norms. The analysis focuses on four interrelated layers of the concept: emotional (affection, intimacy), axiological (loyalty, honesty, moral duty), cognitive-associative (conceptual networks and oppositions), and linguistic (lexical choices, collocations, phraseology, and paremiology). The findings show that Uzbek conceptualization of friendship tends to be “heart-centered,” foregrounding loyalty, devotion, and communal responsibility, while English conceptualization is more “choice-centered,” emphasizing voluntary affiliation, trust, and interpersonal boundaries. These differences create predictable translation risks—undertranslation of axiological force into English and overneutralization or pragmatic mismatch into Uzbek—especially in idioms and proverbs. The article proposes a translation-oriented framework that prioritizes conceptual and functional equivalence, supported by strategies such as axiological compensation, functional substitution, and selective explicitation. The results contribute to translation theory by strengthening the case for concept-based equivalence and offer practical guidance for translators and translation pedagogy in intercultural contexts.